PERANCANGAN SISTEM PENGELOMPOKAN DAN REKOMENDASI SAHAM LQ45 DENGAN K-MEDOIDS, EXPONENTIAL MOVING AVERAGE DAN WEIGHTED PRODUCT - Alvin Chandra; Bagus Mulyawan; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Stock is an instrumentation that has the fundamentalsof a company. Owning a share means owning theshares of the company. Shares can be traded on theIndonesian Stock Exchange by the entire public. TheLQ45 stock grouping and recommendation applicationis a desktop-based application that aims to assist inmaking investment decisions in the Indonesian CapitalMarket. The application is designed using the Pythonprogramming language. The application applies the KMedoidsClustering method to group stocks andExponential Moving Average along with WeightedProducts to make recommendations or sort shares.Users can enter the desired share criteria and theapplication will recommend according to the inputcriteria from the user. Testing on this application iscarried out by the BlackBox testing method,questionnaire, K-Medoids Algorithm Testing and theoutput results of the program. From the results of theblack box testing, the application results can runaccording to plan. In testing the K-Medoids Algorithm,the results obtained that the number of clustersdetermined are in accordance with the number of 2clusters using the elbow method. And in testing theoutput results of the program, the results obtained arethe recommendation accuracy of 80.8%.